2019
DOI: 10.3390/su11123305
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Ecology of the Rare Plant Species Verbascum dingleri: Implications for Species Conservation

Abstract: Verbascum dingleri Mattf and Stef. is a Greek endemic plant species belonging to the family of Scrophulariaceae that only occurs in northeastern Greece, east of the city of Kavala. Knowledge of species distribution, habitat requirements, reproduction, ecology, and population characteristics is limited in the literature. In this study, habitat characteristics, population counts, fruit and seed diversity, and germination were studied for the first time. The results indicate that the species geographical distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Thus, seeds of V. phyrigium tolerate a range of pH in tissue culture conditions (5.5-7.0). There are similar studies showing that Verbascum genus grow in different pH ranges [46,47].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, seeds of V. phyrigium tolerate a range of pH in tissue culture conditions (5.5-7.0). There are similar studies showing that Verbascum genus grow in different pH ranges [46,47].…”
Section: Resultssupporting
confidence: 65%
“…(Scrophulariaceae) is endemic to Anatolia and only grows in the Kütahya, Konya, İzmir and Afyon provinces [20]. Verbascum species are grow in a wide variety of habitats, including rocky mountains, meadows, open forests, roadsides and river banks [21][22][23]. The potential of Verbascum species to accumulate many elements in its organs were revealed in earlier studies [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis was performed by the SPSS ® software v. 23.0 (SPSS Inc., Chicago, IL, USA). The percentage values of seed germination and root regenerative ability, were arcsine-transformed to match the normality and homogeneity assumptions (Ganatsas et al 2019). One-way ANOVA was used to test significant differences between the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although an earlier study (Stanton et al 2012) concluded that the highest germination (38%) of S. elaeagnifolium was achieved at alternating temperature 25/15 °C, in the current experiment we chose to study the effect at a constant temperature of 25 ± 1 °C and a photoperiod of 12 hours. Seeds in each treatment were watered as needed to pro-vide seeds with an adequate moisture level (Ganatsas et al 2019), respectively with a leaf extract of each of the five tree species, while in the control treatment the seeds watered with distilled water. Every 2 nd day the seeds were checked for germination and fungus infection for a duration of 45 days.…”
Section: First Experimentsmentioning
confidence: 99%
“…The experiments were carried out in a temperature-controlled growth chamber at 20 ± 0.5 • C with a photoperiod of 12 h and luminance of 1000 lux [20]. Seeds were watered, as needed to provide seeds with an adequate moisture level [21], with distilled water. Every second day the seeds were checked for germination and fungus infection for 45 days duration.…”
Section: Seed Germination Trialmentioning
confidence: 99%